EP683 Management of pregnancy after fertility-sparing surgery for cervical cancer. (1st November 2019) - Slama, J; Simjak, P; Cibula, D; Parizek, A
Abstract : Introduction/Background: Cervical cancer is increasingly diagnosed in women who have not yet completed their reproductive plans. For these patients with stages IA2 and IB1 cervical cancer, trachelectomy is the treatment of choice. However, patients who undergo repeated conization or trachelectomy represent a challenge for obstetricians as they are at increased risk of infertility, mid-trimester abortion, preterm premature rupture of membranes and preterm delivery. Methodology: So far, the evidence-based guidance on the management of these pregnancies is limited because good-quality studies conducted on this specific population are lacking. Most recommendations originated from underpowered observational studies or are extrapolated from studies conducted in other specific groups of patients, such as patients with cervical incompetence. Results: Screening and treatment of asymptomatic bacteriuria and screening for cervical incompetence and progressive cervical shortening by transvaginal ultrasonography and proper usage of fetal fibronectin test is desirable in patients after FSS for early stages of cervical cancer. Vaginal progesterone supplementation should be administered to all women after vaginal trachelectomy. It should also be administered to women with asymptomatic short cervix after cervical conization. Women with a prior history of preterm delivery or late miscarriage may benefit from cervical cerclage if they have a short cervix after conization or underwent trachelectomy. The delivery is to be carried out by cesarean section in patients after trachelectomy, even in cases of preterm delivery. Conclusion: The management of pregnancy in women after FSS is not uniform, which is not surprising given the lack of evidence-based data. Most recommendations so far are derived from personal experience, underpowered observational studies or are extrapolated from studies conducted in other specific groups of patients, such as patients with cervical incompetence. As pregnancies after FSS become more common, providing guidance for clinicians is worthwhile. Disclosure: Nothing to disclose.